Field evaluation of TaDREB2B-ectopic expression sugarcane (Saccharum spp. hybrid) for drought tolerance - Xiao, Shenghua; Wu, Yang; Xu, Shiqiang; Jiang, Hongtao; Hu, Qin; Yao, Wei; Zhang, Muqing (Frontiers in Plant Science, 2022)
Sugarcane is one of the most crucial sugar crops globally that supplies the main raw material for sugar and ethanol production, but drought stress causes a severe decline in sugarcane yield worldwide. Enhancing sugarcane drought resistance and reducing yield and quality losses is an ongoing challenge in sugarcane genetic improvement. Here, we introduced a Tripidium arundinaceum dehydration-responsive element-binding transcription factor (TaDREB2B) behind the drought-responsible RD29A promoter into a commercial sugarcane cultivar FN95-1702 and subsequently conducted a series of drought tolerance experiments and investigation of agronomic and quality traits. Physiological analysis indicated that Prd29A: TaDREB2B transgenic sugarcane significantly confers drought tolerance in both the greenhouses and the field by enhancing water retention capacity and reducing membrane damage without compromising growth. These transgenic plants exhibit obvious improvements in yield performance and various physiological traits under the limited-irrigation condition in the field, such as increasing 41.9% yield and 44.4% the number of ratooning sugarcane seedlings. Moreover, Prd29A: TaDREB2B transgenic plants do not penalize major quality traits, including sucrose content, gravity purity, Brix, etc. Collectively, our results demonstrated that the Prd29A-TaDREB2B promoter-transgene combination will be a useful biotechnological tool for the increase of drought tolerance and the minimum yield losses in sugarcane.